Prevention and Treatment of Cytomegalovirus Infection in Transplant Recipients - Jutta K Preiksatis (Canadian Journal of Infectious Diseases)
Over the past decade, significant progress has been made in the understanding of the molecular biology of cytomegalovirus (CMV) and the pathogenesis of CMV infection and disease. The introduction of antiviral agents with efficacy against CMV, coupled with rapid diagnostic techniques in the laboratory, have resulted in the design of a number of regimens lo prevent, modify and treat CMV infections in transplant recipients. Strategies for preventing CMV infection, including donorrecipient matching, the use of CMV 'safe' cellular blood products, passive and active immunization, and prophylactic antiviral drugs are discussed. Clinical trials of antiviral drugs alone. or in combination with immunoglobulin for the treatment of CMV disease are reviewed.